The applications of odd meters and reharmonization in progressive jazz metal case study: pink panther arrangement by panzerballett / Tg Muhd Ridzuan Shah Tg Abd Halim - Tg Abd Halim, Tg Muhd Ridzuan Shah (2010)
Progressive Jazz Metal is a result of an evolutionary hybrid of genres. It is basically a combination of progressive metal and jazz music. The applications of various aspects of music theory mainly are influenced by jazz music. Though the genre may have the main elements of metal that similar to rock such as heavy distortion sound produce and energetic drums playing, it still represents the jazz elements by the characteristics of the music genre itself. Panzerballett is one Progressive Jazz Metal band. Panzerballett are Jan Zehrfeld as guitarist, Martin Mayrhofer as second guitarist, Gregor Burger, saxophone, Alexander v. Hagke, saxophone, Heiko Jung, the bassist, and Sebastian Lanser as the drummer. the purpose of why I chose the band as my reference for my research was because I considered that Panzerballett is the one which has the responsibility to evolve of this evolutionary hybrid of genre. This band mostly represents the main characteristics of Progressive Jazz Metal. Through my research, I have investigated in seeking the main characteristics of Progressive Jazz Metal and how would they be applied into an arrangement through a detailed analysis of one composition: Pink Panther; arrangement by Panzerballett and as well as Henry Mancini's arrangement. Thus my point of concern focuses on: the application of odd meter and reharmonization.